Analisis Nilai Wajar Saham Dengan Metode Price Earning Ratio - Murtaji Murtaji (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2022)
Stock investment analysis can be done by fundamental analysis and technical analysis. This study aims to analyse fair value (intrinsic value) of stock by using one of the fundamental technique, i.e. price earning ratio (PER). This study uses four fundamentals indicator such as return on equity (ROE), earning per share (EPS), dividend per share (DPS), and dividend payout ratio (DPR). Research sample are determined by purposive sampling technique. This research analyze two go-public companies that listed in Indonesia Stock Exchange, i.e. PT Adhi Karya (Persero) Tbk and PT Wijaya Karya (Persero) Tbk. Those companies are listed in Indonesia Stock Exchange with stock code ADHI and WIKA. The results of this study are both PT Adhi Karya (Persero) Tbk and PT Wijaya Karya (Persero) Tbk stock’s are in overvalued condition, so the investment decision that can be taken are sell those stock.